ANALISIS DATA DAN INFORMASI KASUS ILLEGAL LOGGING YANG DITANGANI OLEH SPORC BRIGADE BEKANTAN DENGAN MENGGUNAKAN APLIKASI CASE TRACKING DATABASE - Nursyahdi, Arrafi; Dewantara, Iswan; Oramahi, HA (Universitas Tanjungpura, 2013)
Handling of illegal logging efforts undertaken by the SPORC Brigade Bekantan is still considered to be less significant results. One due to the lack of monitoring systems and data handling cases of illegal logging and information effectively and efficiently. It has been developed within the framework of Case Tracking Database Application which aims to integrate all the data and information of illegal logging cases ranging from criminal detection process until settlement in court. This study aims to identify and analyze the data and information that illegal logging cases handled by SPORC Brigade Bekantan. This research method is descriptive of the data and information that illegal logging cases handled by the SPORC Brigade Bekantan from 2006 to 2012 were collected by the study documentation for further processed and analyzed by the application of Case Tracking Database. Interpretation of the results is done so as to obtain a conclusion that is used to monitor the progress of cases handled by illegal logging. From the data processing and information illegal logging cases, it is known that there are as many as 73 reported incidentsby the suspect as many as 82 people and as many as 149 units of evidenc.A total of 72 cases or 99% were carried out while the investigation process for resolving cases as much as 85% or 62 cases that had P-21 and for data only 16 verdict or the case only reached 22%. Evidence of the amount of logs and processed wood, total non-tax revenue of the auction proceeds of Rp.3.618.025.000,-, while the economic losses that should be obtained from PSDH, DR and replacementstumpage valueof Rp.1.998.446.339,-. Keywords:Interpretation, Case Tracking Database, SPORC Brigade Bekantan